Bacteriological quality and food hygiene: A descriptive cross-sectional study of street restaurants on the University of Kinshasa campus, Democratic Republic of the Congo - Lipemba Ngonzili, Jean; Bolia Ebolo , Faustin; Manitu Basosa , Destin; Disuemi Bisita , Emérite; Kaswij Muswiya, Fraste; Mata Kimbembe , Henry (Orapuh Journal, 2025)
IntroductionEating is a fundamental human need essential for survival, development, and wellbeing. Consumers have the right to safe food that does not pose a health risk.PurposeTo assess the bacteriological quality and food hygiene of meals sold in restaurants on the University of Kinshasa campus.MethodsWe conducted a cross-sectional descriptive study between July and November 2024. A two-stage sampling strategy was applied to select campus restaurants. Food samples were subjected to bacteriological analysis and restaurant hygiene practices were evaluated. Bacteriological quality was compared with international standards. Continuous variables were summarised as medians and interquartile ranges, while categorical variables were presented as frequencies and percentages.ResultsMost respondents (93.7%) were women; 87.5% had no formal training in food hygiene; 87.5% did not wear personal protective equipment; and 68.8% washed their hands only 1–2 times per day. Over half (56.3%) used buckets as waste bins. Of 32 food samples analysed, 81.2% were contaminated with Escherichia coli, 78% with total coliforms, 34.3% with mesophilic aerobes, and 9.4% with enterococci. At least one food item from restaurants in Zones A and C contained all the microorganisms tested.ConclusionBacteriological quality and food hygiene in University of Kinshasa campus restaurants are unsatisfactory, exposing consumers to potentially severe foodborne diseases that could negatively impact their academic performance. Capacity building for food handlers and regular inspections are urgently needed.